Аналіз використання технологій блокчейн для розподіленої обробки і зберігання даних - Кураков, Я. С.; Колтун, Ю. М. (ХНУРЕ, 2025)
This work analyzes the use of blockchain technologies for distributed data processing and storage on the example of Ethereum and Hyperledger platforms. In the course of the analysis, the main problems associated with these processes, as well as with the transmission of sensitive data through data transmission networks, are highlighted. It is shown that most of them can be mitigated by applying appropriate algorithms, such as the Proof-of-Work (PoW) algorithm. The Network Simulator (NS-3) together with the Bitcoin Simulator framework has been used to model the environment. PoW blockchains containing several hundred network devices in close geographical proximity have been found to achieve the highest performance.
Keywords: блокчейн; зберігання даних